A Modified ω- k Algorithm for HS-SAR Small-Aperture Data Imaging - Liang, Yi; Huai, Yuanyuan; Ding, Jinshan; Wang, Hongxian; Xing, Mengdao (IEEE transactions on geoscience and remote sensing, 2016)
Due to the skew data support region (DSR) of the 2-D wavenumber spectrum for high-squint synthetic aperture radar (HS-SAR), the conventional w-k algorithm cannot fully utilize the DSR and thus degrades the resolution if simply taking a rectangle region. Meanwhile, for the small-aperture data, direct azimuth imaging in the distance domain will lead to serious aliasing. A modified ω-k algorithm is derived in this paper to solve these problems. The maximum usage of DSR is achieved by the coordinate rotation. As for the azimuth dependence, the method of azimuth resampling is used to get the uniform focusing. Different from the traditional w-k method, the modified w-k algorithm focuses the small-aperture data in the azimuth wavenumber domain by SPECAN processing, which avoids padding a large number of zeros when imaging in the azimuth distance domain. Simulated and real-data results show the validity and effectiveness of the presented algorithm.